Male‐mediated prenatal loss: Functions and mechanisms. Issue 3 (6th April 2019) - Zipple, Matthew N.; Roberts, Eila K.; Alberts, Susan C.; Beehner, Jacinta C.
ABSTRACT: Sexually selected infanticide has been the subject of intense empirical and theoretical study for decades; a related phenomenon, male‐mediated prenatal loss, has received much less attention in evolutionary studies. Male‐mediated prenatal loss occurs when inseminated or pregnant females terminate reproductive effort following exposure to a nonsire male, either through implantation failure or pregnancy termination. Male‐mediated prenatal loss encompasses two sub‐phenomena: sexually selected feticide and the Bruce effect. In this review, we provide a framework that explains the relationship between feticide and the Bruce effect and describes what is known about the proximate and ultimate mechanisms involved in each. Using a simple model, we demonstrate that male‐mediated prenatal loss can provide greater reproductive benefits to males than infanticide. We therefore suggest that, compared to infanticide, male‐mediated prenatal loss may be more prevalent in mammalian species and may have played a greater role in their social evolution than has previously been documented.